Determinants of the severity of household food insecurity among the slums of Dhaka city, Bangladesh. Issue 2 (4th May 2021) - Bhattacharjee, Poushali; Sassi, Maria
ABSTRACT: According to the National Food Policy of Bangladesh, the urban slum dwellers are the most vulnerable group to ensure food security. Their condition has not been materially improved over three decades. In our study, we present the current food insecurity scenario in the slums of Dhaka city using the most recent 'Bangladesh – Urban Informal Settlements Baseline Survey' dataset of the World Bank. Afterwards, we analyse the determinants of the household food calorie gap by applying the Inverse Hyperbolic Sine transformed Double Hurdle model. The determinants are organised to represent the three pillars of food security (food availability, access, and utilisation) and all three pillars have emerged as significant factors in determining the food calorie gap. From our empirical results, we highlight some vital gaps in the National Food Policy and recommend broad areas of interventions for the betterment of the food security status among the slum dwellers of Dhaka.